Correlation of the complementary virtual test of computer-simulated clinical cases with the classic OSCE and with the MIR score. - Naranjo Hernandez, Antonio; Boronat, Mauro; Rodríguez, Pedro Miguel; Martín, Alicia; Castro, Antonio; Ramos Rincón, José Manuel; Reyes, Desiderio (Spanish Journal of Medical Education, 2026)
Introduction. Starting in 2021, Spanish medical schools were offered a Complementary Virtual Clinical Examination (CVCE) with computer-simulated clinical cases, sponsored by the National Conference of Deans. This study analyzes the correlation between CVCE scores, the local OSCE with simulated patients and mannequins, the clinical rotation score, and the results of the MIR exam. Methods. An observational correlation study was conducted, including students evaluated between 2021 and 2025 at the University of Las Palmas de Gran Canaria. Correlations were analyzed using Pearson and Spearman coefficients. Results. 652 students were included, with MIR data available for 2022. The correlation between the local OSCE and the CVCE and the MIR was weak (Rho = 0.26; p<0.001 and Rho = 0.31; p<0.001, respectively). The correlation between the Clinical Clinical Practice Assessment (CCP) and the Medical Residency Exam (MIR) was moderate and consistent over the five years (r = 0.56; p < 0.001). No correlation was found between the clinical rotation score and the CCP, the OSCE, or the MIR. Women performed better in the local OSCE history taking and in the clinical rotation, while men performed better in the CCP and the MIR. Conclusions. The CCP correlates more consistently with the MIR than the local OSCE, suggesting greater predictive value. The results suggest that the MIR and the local OSCE assess different domains of clinical competence, highlighting the complementary and exploratory nature of the skills each test evaluates.